2022
DOI: 10.1007/s00296-022-05229-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 severity and vaccine breakthrough infections in idiopathic inflammatory myopathies, other systemic autoimmune and inflammatory diseases, and healthy controls: a multicenter cross-sectional study from the COVID-19 Vaccination in Autoimmune Diseases (COVAD) survey

Abstract: Objectives We aimed to compare the spectrum and severity of COVID-19 and vaccine breakthrough infections (BIs) among patients with IIMs, other systemic autoimmune and inflammatory diseases (SAIDs), and healthy controls (HCs). Methods This is a cross-sectional study with data from the COVAD study, a self-reported online global survey that collected demographics, COVID-19 history, and vaccination details from April to September 2021. Adult patients with at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…Regarding immunosuppressive treatment, the duration of therapy, the type of drugs, and the dose of glucocorticoids are important factors that may differently affect the disease course 4–7 . Lastly, the response to COVID‐19 vaccines could be less efficient in AIRD patients due to immunosuppressive treatment or underlying immune dysregulation 7,8 . This may contribute to the more severe disease course in AIRD patients despite vaccination.…”
Section: The Factors Possible Effects On Covid‐19 Outcomementioning
confidence: 99%
“…Regarding immunosuppressive treatment, the duration of therapy, the type of drugs, and the dose of glucocorticoids are important factors that may differently affect the disease course 4–7 . Lastly, the response to COVID‐19 vaccines could be less efficient in AIRD patients due to immunosuppressive treatment or underlying immune dysregulation 7,8 . This may contribute to the more severe disease course in AIRD patients despite vaccination.…”
Section: The Factors Possible Effects On Covid‐19 Outcomementioning
confidence: 99%
“…Infections with Omicron were observed across India from January 2022 onwards [ 2 ]. Previous studies had shown a modest decline in vaccine effectiveness against the delta variant from the original alpha strain in terms of breakthrough infections [ 3 6 ]. Patients with autoimmune rheumatic diseases are at increased risk for severe COVID-19 due to their medications and prevalent comorbidities [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We appreciate that disease activity is an aspect that we would like to explore as it is likely to be relevant to outcomes, and hope that some ongoing studies with big-datasets answer these important questions. [3] , [4] , [5] With successful worldwide global vaccination, pre-vaccination outcomes are harder to explore and persistent hesitancy as well as infection induced flares may be more pertinent questions to explore. SARS-CoV2 epitopes have been identified to bear sequence homology with T cell receptors in dermatomyositis, substantiating plausible links between viral triggers for autoimmunity.…”
mentioning
confidence: 99%
“…Hoff et al identified higher odds of breakthrough infection in IIM patients receiving intense immunosuppression, reiterating that immunosuppression defined risk stratification would be an ideal approach to inform booster dose schedules. 3 We would be interested in exploring data on antibody response to previous COVID-19 infection and vaccination and its interplay with immunosuppressant received in different subtypes of DM. We hope that despite the rarity of this condition and ethnic and environmental factors that may be at play, big datasets set in the real world offer insights in this direction.…”
mentioning
confidence: 99%
See 1 more Smart Citation